Da invisibilidade à ascensão social: história e memória de professores negros no Amapá: 1970-1988 - Maciel, Alexsara (2014)
This research discusses and analyzes the life trajectory of black teachers in basic school and high school in the 1970s up to 1988, who were born, alphabetized and became teachers in Amapá Federal Territory. Within this period, they built up a teaching carrier working in different city schools and consolidated the acknowledgement of their teaching job through the social acknowledgement they achieved and keep up to nowadays in Amapá social means. The paper was built upon an oral history approach, using interviews with black teachers who worked during the 1970s and 1980s in many schools in Macapá city. Our goal was to contribute to widenning studies on education of black people in Amapá and to give these people who helped to make up education in Amapá voice, emphasizing the perception of race segregation in this State and the uniqueness of the social rising achieved by the interviewees due to their teaching job. When (re)building the history of their lives, we met meanings which are often ignored by those who are out of the process, considering the singularity and the experiences lived in the region. The research showed aspects of inequality among black people that point to greater difficulties in achieving social rise through education, what is indicated by the narratives.